Concussion-Related Vision Disorder Practice Patterns in Occupational Therapy: A Survey - Alicia Reiser; Greta Bunin; Mitchell Scheiman (Scholarworks @ WMU, 2020)
Background: Occupational therapists are among the first providers to initiate care after a concussion; however, evidence is limited regarding current concussion-related vision disorder practice patterns. A better understanding of these practice patterns is important because of the impact of undetected and untreated vision problems on occupational performance. Method: A mixed-methods survey was administered online to occupational therapists to explore the assessments and interventions used to address concussion-related vision disorders, occupational therapy's perceived role, and difficulties encountered when treating these conditions. Results: Of 23,910 occupational therapists invited to participate, 2,278 (10%) began the survey, and 1,187 (52%) met inclusion criteria. Assessment tools identified were subjective and objective in nature. Identification and treatment varied significantly based on years of practice, whether an optometrist was on site, and whether vision continuing education was completed. Identified roles included ADLs, compensation, and identification. Treatment difficulties included resources, education, and evidence. Conclusion: Data revealed inconsistent practice patterns, perhaps because of educational differences. The results suggested improving education in the areas of concussion and vision by developing interprofessional collaboration and standards of care, developing a vision remediation certification, and producing further research regarding concussion-related vision disorders and occupation in the occupational therapy literature.